2022
DOI: 10.3390/agronomy12040791
|View full text |Cite
|
Sign up to set email alerts
|

Does Phosphorus Fertilization Increase Biomass Production and Salinity Tolerance of Blue Panicum (Panicum antidotale Retz.) in the Salt-Affected Soils of Arid Regions?

Abstract: High soil salinity, drought, and poor soil fertility, especially phosphorus (P) deficiency, are serious challenges for crop production in arid and desert climate regions. In these regions, irrigation water (mostly groundwater) is saline, and fertilization is one of the strategies used to cope with salinity stress. Crop livestock is one of the major agricultural activities in marginal regions, and blue panicum (Panicum antidotale Retz.), the perennial forage grass, has the potential to furnish forage demand. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Their obtained results revealed no significant difference between the tested salinity levels in terms of biomass yield which indicate that the salinity tolerance threshold of blue panicgrass is probably beyond 10 dS.m -1 . In a recent study conducted under similar pedo-climatic conditions as the present experiment (Foum Eloued), Bouras et al (2022) reported that the annual fresh biomass yield was reduced by 18% and 25% under irrigation water salinity of 12 and 17 dS•m −1 , respectively, compared to the control.…”
Section: Introductionsupporting
confidence: 63%
“…Their obtained results revealed no significant difference between the tested salinity levels in terms of biomass yield which indicate that the salinity tolerance threshold of blue panicgrass is probably beyond 10 dS.m -1 . In a recent study conducted under similar pedo-climatic conditions as the present experiment (Foum Eloued), Bouras et al (2022) reported that the annual fresh biomass yield was reduced by 18% and 25% under irrigation water salinity of 12 and 17 dS•m −1 , respectively, compared to the control.…”
Section: Introductionsupporting
confidence: 63%
“…The effects of salt stress are increasing due to lower rainfall and higher atmospheric temperature, which are major reasons for lower productivity globally [3,4]. Soil salinity induces various Plants 2023, 12, 1644 2 of 16 negative impacts in plants ranging from reduction in germination to seedling vigor and vegetative growth [5,6]. Salinity stress also disturbs the plant's functioning and induces ROS production, which damage membranes, and proteins and causes a reduction in nutrient uptake and subsequent growth [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the decrease in Ca in this research differs from the findings of Freitas et al (2011) in Panicum maximum Jacq, who attributed the decrease in foliar Ca with the increase in the P dose due to the dilution effect when the plant is more fertilized. Bouras et al (2022), in Panicum antidotale at soil with a pH of 8.7, found no differences in foliar Ca concentration after applying between 0 and 108 kg/ ha of P in the form of P 2 O 5 .…”
Section: Calciummentioning
confidence: 86%